1990
DOI: 10.1007/bf01310620
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polypeptides synthesized in bovine respiratory syncytial virus-infected cells

Abstract: Ten virus-specific polypeptides ranging in molecular weight from approximately 200k to 11k were identified in bovine respiratory syncytial virus (BRSV-)infected cells. Time course analysis of the induction of the viral polypeptides indicated that they could be detected as early as 30 min post-infection and their synthesis reached a plateau 12 h after infection. Cell free translation of total infected-cell mRNA in a rabbit reticulocyte system yielded 7 proteins corresponding in size to virus-specific proteins s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
3

Year Published

1992
1992
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
3
23
0
3
Order By: Relevance
“…The predicted protein is 241 amino acids long, identical in length to the P proteins of HRSV. It has a calculated Mr of 27 208, whereas that calculated previously from SDS-polyacrylamide gels is 34K (Mallipeddi et al, 1990). Similar discrepancies have also been found between the calculated Mr and that deduced from the mobility of HRSV P proteins in gels (Johnson & Collins, 1990).…”
mentioning
confidence: 46%
See 1 more Smart Citation
“…The predicted protein is 241 amino acids long, identical in length to the P proteins of HRSV. It has a calculated Mr of 27 208, whereas that calculated previously from SDS-polyacrylamide gels is 34K (Mallipeddi et al, 1990). Similar discrepancies have also been found between the calculated Mr and that deduced from the mobility of HRSV P proteins in gels (Johnson & Collins, 1990).…”
mentioning
confidence: 46%
“…Although BRSV and HRSV are antigenically related, they differ in their pattern of reactivity with monoclonal antibodies (Mufson et al, 1985;()rvell et al, 1987;Beeler & van Wyke Coelingh, 1989). It has been shown that like that of HRSV, the genome of BRSV encodes 10 mRNAs (Lerch et al, 1989), and that the protein composition of these viruses is very similar, with only minor differences in Mr between corresponding proteins (Cash et al, 1977;Lerch et al, 1989;Trudel et al, 1989;Mallipeddi et al, 1990). To delineate the genetic basis for the differences between HRSV and BRSV, we and others have undertaken cDNA cloning and nucleotide sequencing of BRSV genes for comparison with the sequences of the genes of HRSV.…”
mentioning
confidence: 99%
“…For these reasons, recombinant BRSV proteins are more suitable for use as antigens in diagnostic ELISA. The N protein of BRSV appears to be an ideal candidate for use as an antigen in diagnostic ELISA, since it is the most abundant viral protein in BRSV-infected cells [12,13] and antibodies to the N protein appear early and predominate during BRSV infection [25].…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type baculovirus, and recombinant baculoviruses were plaquepurified and propagated as described by Summers and Smith (1987) [21]. The construction and characterization of the recombinant baculovirus encoding the BRSV N protein were accomplished by established methods as described before [13,17].…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation